Extremely low frequency electromagnetic stimulation reduces ischemic stroke volume by improving cerebral collateral blood flow. Issue 6 (June 2022) - Kemps, Hannelore; Dessy, Chantal; Dumas, Laurent; Sonveaux, Pierre; Alders, Lotte; Van Broeckhoven, Jana; Font, Lena Perez; Lambrichts, Sara; Foulquier, Sébastien; Hendrix, Sven; Brône, Bert; Lemmens, Robin; et al.
Extremely low frequency electromagnetic stimulation (ELF-EMS) has been considered as a neuroprotective therapy for ischemic stroke based on its capacity to induce nitric oxide (NO) signaling. Here, we examined whether ELF-EMS reduces ischemic stroke volume by stimulating cerebral collateral perfusion. Moreover, the pathway responsible for ELF-EMS-induced NO production was investigated. ELF-EMS diminished infarct growth following experimental stroke in collateral-rich C57BL/6 mice, but not in collateral-scarce BALB/c mice, suggesting that decreased lesion sizes after ELF-EMS results from improved collateral blood flow. In vitro analysis demonstrated that ELF-EMS increased endothelial NO levels by stimulating the Akt-/eNOS pathway. Furthermore, ELF-EMS augmented perfusion in the hind limb of healthy mice, which was mediated by enhanced Akt-/eNOS signaling. In healthy C57BL/6 mouse brains, ELF-EMS treatment increased cerebral blood flow in a NOS-dependent manner, whereas no improvement in cerebrovascular perfusion was observed in collateral-sparse BALB/c mice. In addition, ELF-EMS enhanced cerebral blood flow in both the contra- and ipsilateral hemispheres of C57BL/6 mice subjected to experimental ischemic stroke. In conclusion, we showed that ELF-EMS enhances (cerebro)vascular perfusion by stimulating NO production, indicating that ELF-EMS could be an attractive therapeutic strategy for acute ischemic stroke by improving cerebral collateral blood flow.